The Goldilocks principle in action: synthesis and structural characterization of a novel {Cu4(?3-OH)4} cubane stabilized by monodentate ligands - Ardizzoia, G. Attilio; Brenna, Stefano; Durini, Sara; Therrien, Bruno; Trentin, Ivan (My University, 2013)
A {Cu4(?3-OH)4} compd., where four Cu(II) and four ?3-bridging O atoms occupy alternate corners of a slightly distorted cube, was prepd. and structurally characterized. This species, formulated as [Cu4(?3-OH)4(Htmpz)8](ClO4)4·1.5Et2O (Htmpz = 3,4,5-1H-trimethyl pyrazole), can be classified as belonging to type I Cu4O4 cubane complexes, and is better described as two CuII-(?-OH)2-CuII units held together by four long Cu-O bonds. The central distorted cubane core is stabilized by neutral monodentate ligands (Htmpz) and perchlorate anions, as demonstrated by single-crystal x-ray structure anal. The title compd. was obtained by hydrolysis of a dinuclear methoxo-bridged species, [Cu(?-OCH3)(Htmpz)2]2(ClO4)2, which was prepd. by reaction of [Cu(Htmpz)4(ClO4)2] with MeOH. All these reactions represent a nice example of the Goldilocks principle in action in coordination chem., since each single actor (solvent, counteranion, and ligand) has the just right electronic, steric or coordinative properties which det. the fate of the final products. [on SciFinder(R)]
Keywords: methoxo bridged dinuclear copper pyrazole complex prepn hydrolysis; crystal structure tetranuclear copper hydroxide cubane pyrazole complex prepn